The inclusion of grothite in the zircon from granitoids of the crystalline basement of the Southern Yamal Peninsula - Erokhin Yu. V.; Ivanov K. S.; Khiller V. V. (Vestnik MGTU, 2019)
Grothite – rare F-Al-rich type of titanite – has been found in accessory zircon from the granitoids of the pre-Jurassic basement of the Verkhnerechensky oil-gas area (in the southern part of the Yamal Peninsula) as a result of the study. Titanite forms rare inclusions (so-called minerals-prisoners) in the central parts of zircon crystals; in our sample of 35 individuals only two grains of titanite have been discovered. The measurement of the chemical composition of the mineral has been carried out on an electron-probe microanalyzer CAMECA SX 100, equipped with five wave spectrometers (IGG UrB RAS, Ekaterinburg). According to the microprobe analysis, the mineral has an unusual chemical composition, it shows the presence of significant concentrations of alumina (Al2O3 to 8.5 wt.%), rare earths elements (REE to 4.3 wt.%), and fluorine (F to 2 wt.%). This grothite is dramatically different in chemical composition from the accessory titanite of the matrix granitoid (monzoleicogranite), which is characterized by values close to the reference sphene. Overall, grothite is an intermediate connection between the two extreme members CaTiSiO4O (titanite) – CaAlSiO4F (synthesized Al-F-titanite), and the Verkhnerechensky mineral content of a hypothetical Al-F-titanite achieves a high level of 24–26 %. Unfortunately, grothite is crystallized in a wide range of temperatures and pressures which does not allow its use in thermodynamic reconstructions. The existence of grothite (or Al-F-titanite) is apparently determined not so much on the PT-conditions of rocks' formation, but most likely on the chemistry of the environment. So it is obvious that the Verkhnerechensky titanite was formed in the melt with an increased concentration of fluorine. It is the first record of grothite in the form of inclusions in accessory zircon.